오버헤드 전기 케이블 및 오버헤드 전기 케이블 제작 방법 (2024)
본 발명은 원래의 오버헤드 전기 케이블 및 오버헤드 전기 케이블을 제작하기 위한 방법에 관한 것이다. 전기 케이블은 강도 부재 및 강도 부재를 둘러싸는 2개 이상의 전도층들을 포함하되, 이 두 전도층들은 각각 제1 및 제2 전도 스트랜드들로 형성된다. 제1 전도 스트랜드들은 제1 알루미늄 재료로 형성되고 제2 전도 스트랜드들은 제2 알루미늄 재료로 형성되며, 제2 알루미늄 재료는 제1 알루미늄 재료의 재료 특성과 상이한 하나 이상의 재료 특성을 가진다. 예를 들어, 제2 전도 스트랜드들은 제1 알루미늄 재료보다 높은 경도를 가지지만 제1 알루미늄 재료보다 낮은 전도성을 가진 알루미늄 재료로 형성될 수 있다. 이러한 형상은, 오버헤드 전기 케이블이 높은 빙설 하중이 제공되는 지리적 지역에 설치될 때 특히 유용할 수 있다. A bare overhead electrical cable and a method for the manufacture of an overhead electrical cable. The electrical cable includes a central strength member and at least two conductive layers surrounding the strength member, the two conductive layers being formed from first and second conductive strands respectively. The first conductive strands are formed from first aluminum material and the second conductive strands are formed from a second aluminum material, where the second aluminum material has at least one material property that is different than the same material property of the first aluminum material. For example, the second conductive strands may be formed from an aluminum material having a lower conductivity but higher hardness than the first aluminum material. Such a configuration may be useful when the overhead electrical cable is installed in a geographic region that is subject to heavy ice loading.